Factors determining the potential for onward transmission of variant Creutzfeldt–Jakob disease via surgical instruments - Garske, Tini (The Royal Society, 2006)
While the number of variant Creutzfeldt–Jakob disease (vCJD) cases continues to decline, concern has been raised that transmission could occur directly from one person to another through routes including the transfer of blood and shared use of surgical instruments. Here we firstly present data on the surgical procedures undertaken on vCJD patients prior to onset of clinical symptoms, which supports the hypothesis that cases via this route are possible. We then apply a mathematical framework to assess the potential for self-sustaining epidemics via surgical procedures. Data from hospital episode statistics on the rates of high- and medium-risk procedures in the UK were used to estimate model parameters, and sensitivity to other unknown parameters about surgically transmitted vCJD was assessed. Our results demonstrate that a key uncertainty determining the scale of an epidemic and whether it is self-sustaining is the number of times a single instrument is re-used, alongside the infectivity of contaminated instruments and the effectiveness of cleaning. A survey into the frequency of re-use of surgical instruments would help reduce these uncertainties.